2019
DOI: 10.3389/fendo.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Ovarian Granulosa Cells in Health and Disease

Abstract: The granulosa cell (GC) is a critical somatic component of the ovary. It is essential for follicle development by supporting the developing oocyte, proliferating and producing sex steroids and disparate growth factors. Knowledge of the GC's function in normal ovarian development and function, and reproductive disorders, such as polycystic ovary syndrome (PCOS) and premature ovarian failure (POF), is largely acquired through clinical studies and preclinical animal models. Recently, microRNAs have been recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 103 publications
2
60
0
Order By: Relevance
“…As expected, fertility issues could be triggered by defects in folliculogenesis. The normal growth of granulosa cells including proliferation and apoptosis seems to be dysregulated by the interaction of miRNA with the TGF-β signaling pathway ( Chan et al, 2010 ; Zhang Q. et al, 2013 ; Nie et al, 2015 ; Tu et al, 2019 ). Interestingly, it has been reported that Smads, the signal transducers of TGF-β/GDF, could promote a specific set of miRNAs by assisting the cleavage reaction by Drosha.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, fertility issues could be triggered by defects in folliculogenesis. The normal growth of granulosa cells including proliferation and apoptosis seems to be dysregulated by the interaction of miRNA with the TGF-β signaling pathway ( Chan et al, 2010 ; Zhang Q. et al, 2013 ; Nie et al, 2015 ; Tu et al, 2019 ). Interestingly, it has been reported that Smads, the signal transducers of TGF-β/GDF, could promote a specific set of miRNAs by assisting the cleavage reaction by Drosha.…”
Section: Resultsmentioning
confidence: 99%
“…The growth and proliferation of GCs play critical roles in the biological processes of recruitment, selection and maturation of follicles. Several studies demonstrated that the proliferation and apoptosis of GCs were involved in folliculogenesis (Ortega et al, 2012; Tu, Cheung, Chan, & Chan, 2019). FHL2 belongs to the LIM domain‐only proteins and contains four and a half LIM domains (Dahan et al, 2017; McLoughlin, Ehler, Carlile, Licht, & Schafer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…oocyte-cumulus cell interaction, GC function and luteinization by targeting specific molecules and modulating various signaling pathways, such as TGFB-, FSH-, hormone-and apoptosis-related pathways [16,17]. Single nucleotide polymorphisms (SNPs) in miRNAs, including pri-miRNA (primary miRNA transcripts), pre-miRNA (precursor miRNA) and mature miRNA are associated with the abundance of mature miRNA and may contribute to phenotypic variation in animals [13].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%